Does intensive land use decoupled from carbon emissions? an empirical study from the three grand economic zones of China - Zhang, Qingxi; Ge, Jingfeng; Liang, Yanqing; Zhang, Man; Dong, Li; Zhang, Jiazhe (Frontiers in Environmental Science, 2022)
In the context of the increasingly severe global carbon emission crisis, smoothly reducing emissions without affecting economic development and the continuous improvement of people’s living standards has become an important problem facing China, the country with the largest carbon emissions in the world. From the perspective of intensive land use (ILU), this paper uses standard deviational ellipse, decoupling theory, and a logarithmic mean Divisia index (LMDI) model to analyze the level of ILU and carbon emissions in 30 provinces, municipalities, and autonomous regions in China and explores ways to reduce emissions. The results show that: 1) The level of ILU in China’s 30 provinces (municipalities and autonomous regions) has shown steady progress and the overall carbon emissions from land use have shown a slow growth trend, but the carbon emissions of some provinces have shown a downward trend; 2) The ILU and the carbon emissions standard deviational ellipse have good spatial consistency, both of which have a north by east to south by west distribution pattern. The center of the carbon emission standard deviational ellipse moves to the northwest as a whole; 3) 63.33% of provinces are in the ideal decoupling stage of ILU and carbon emissions; 4) According to their contribution value, the influencing factors of China’s carbon emissions are, in descending order, energy intensity, economic scale, population scale, land use structure, energy carbon emission intensity, and land scale. Important directions for future efforts include actively adjusting the industrial structure and economic development mode, increasing the proportion of clean energy and energy utilization rate, controlling the speed of construction and land expansion, and promoting low-carbon emissions.